Assessing Digital Literacy of Batanghari University Students: A Four-Pillar KOMINFO Framework Analysis - Megawati Ananda Putri; Imelda Agustin; Agra Tiadef; Ariaga Dwisura T; Sahal Maghfud; Wahyudi Eka Putra; Daniel Arsa; Mochammad Arief Hermawan Sutoyo (Media Journal of General Computer Science, 2026)
The Society 5.0 era demands comprehensive digital literacy skills encompassing technical competencies, critical thinking, digital ethics, and active participation in digital spaces. This study assesses digital literacy levels of university students at Batanghari University, Jambi Province, using the four-pillar framework developed by the Ministry of Communication and Information Technology, Digital Literacy Activist Network, and Siberkreasi. The research employed quantitative descriptive approach with 100 students from 20 study programs aged 18-29 years. Data was collected through structured questionnaire containing 31 items measuring digital skills, digital safety, digital ethics, and digital culture using 4-point Likert scale. The instrument demonstrated high validity with correlation values above 0.361 and excellent reliability with Cronbach's Alpha of 0.95926. Findings reveal excellent overall digital literacy levels, with 1279 points in "Very High" category and 1034 points in "High" category. Digital Skills showed best performance, followed by Digital Culture, Digital Safety, and Digital Ethics. Results indicate student readiness for Society 5.0 era despite regional internet penetration below national average.